Preface to the first issue of SJORANM - Frank Mosler; Gerd Nöldge (Swiss Journal of Radiology and Nuclear Medicine)
Radiology with its increasing numbers of steadily improving diagnostic and minimal invasive therapeutic methods in combination with the skills of diagnostic and therapeutic procedures in nuclear medicine are meanwhile essential tools on a very high level of patient treatment and care in tight cooperation with the clinicians. Our new Journal (SJORANM) wants to give the chance for quick online access to new ideas, new scientific research and results in the diagnostic and therapeutic field of Radiology and Nuclear Medicine.